Transforming Digital Communication Ethics: An Innovative Strategy to Build a Respectful Virtual Space in Medan Aviation Polytechnic - Muhammad Caesar Akbar; Shafira Ayu Az-zahra (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
The transformation of digital communication has changed the way individuals interact in virtual spaces, including in the world of education. Medan Aviation Polytechnic, as a technology-based educational institution, faces the challenge of maintaining polite communication ethics in the digital space. This research aims to examine how elements such as digital safety, media effectiveness, communication norms, digital empathy, and emotional control shape digital communication ethics in the campus environment. Using a mixed-method approach, data was collected through quantitative surveys, qualitative interviews, and document analysis. The main findings show that digital safety and media effectiveness have a significant impact on the creation of polite communication, while digital empathy and emotional control are key factors in maintaining positive interactions. This article provides recommendations to improve ethical awareness and empathy skills in digital communication at Medan Aviation Polytechnic.